2017
DOI: 10.15419/bmrat.v4i08.205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IgG from multiple sclerosis patients on amidolytic activity of coagulation and anticoagulation factors of hemostasis

Abstract: Background: Immunoglobulin G (IgG) is a major immunoglobulin (Ig) in blood that accumulates to a greater extent in the bloodstream of patients impacted by neuroimmunological disorders such as multiple sclerosis (MS). The aim of this study was to determine the effect of IgG obtained from MS patients on the amidolytic activity of coagulation and on anticoagulation factors, and to compare those effects to the effects of IgG from healthy donors. Methods: Spectrophotometric hydrolysis of specific chromogenic substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Some studies have described the synthesis of antibodies against coagulation components in patients with multiple sclerosis. These antibodies are specific for anticoagulant mediators and serine proteases [29]. We assume that the immune system is able to produce antibodies against abnormal hemostasis components as a result of the violation of proteolysis during post-COVID-19 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described the synthesis of antibodies against coagulation components in patients with multiple sclerosis. These antibodies are specific for anticoagulant mediators and serine proteases [29]. We assume that the immune system is able to produce antibodies against abnormal hemostasis components as a result of the violation of proteolysis during post-COVID-19 conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the development of coagulation disorders is a known consequence of diseases such as viral hepatitis, Epstein-Barr infection, systemic sclerosis, and ischemic stroke by accumulation of autoantibodies. [17][18][19][20] A recent study has reported that autoantibodies can be detected in COVID-19 patients with three types being identified: antiphospholipids, anticytoplasmic neutrophils, and antinuclear antibodies. 21 We determined the dependence of anticoagulation parameters and titers of anti-SARS-CoV-2 IgG in donors who had recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 99%